The Strategic Planning IS/IT to Improve Business Competitiveness in Public Hospital - Muhammad Ridho Bintang Janaputra; Febriliyan Samopa; Rita Ambarwati Sukmono (Universitas Muhammadiyah Malang, 2021)
Hospital competition is getting tighter, making good hospital strategic planning very important so that the Hospital can survive to develop better in a changing environment. Today's competitive advantage cannot be separated from Information Systems (IS) and Information Technology (IT). IS / IT in hospitals is currently used as a tool to create and develop innovative products, systems, and services for hospitals. The problem that occurs today is a large number of IS / IT that is made without looking at the financial side of the Hospital, thus making a number of uses of IS / IT not optimal in Hospital operational and business activities. Based on these problems, IS / IT strategic planning that also considers financial capability is needed. In this research, IS/IT strategic planning that takes into account the financial aspects is achieved using the approach of Ward and Peppard combined with Cost-Benefit Analysis. Value Chain and Critical Success Factor (CSF) analysis methods are used to analyze the current internal condition of the Hospital. Meanwhile, PEST and Porter's Five Forces analysis used external business analysis of the Hospital. The results of this study are in the form of IS business strategy recommendations, IS/IT management strategies, IT strategies, IS application portfolios, and IS/IT investment roadmaps compiled based on costs and benefits. There are 25 IS strategy recommendations, the IT strategy recommends 14 proposals to support the IS strategy based on the cost-benefit, and the IS / IT management strategy recommendations consist of 16 suggestions to support the IS strategy and IT strategy.